PERBEDAAN TINGKAT ADVERSITY QUOTIENT (DAYA JUANG) SISWA SELAMA PEMBELAJARAN DARING DITINJAU DARI TINGKAT PENDAPATAN ORANG TUA DI SMP NEGERI 8 KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack: This study aims to deterimine the differences in the level of adversity quotient of students by high and low income in online learning at SMPN 8 Pekanbaru City. This research method is comparative quantitative conducted at SMPN 8 Pekanbaru. The population in this study were 401 students with cluster random sampling technique and obtained as many as 164 students as a sample. This study uses an adversity quotient questionnaire with a Likert scale. The results of this study indicate the level of adversity quotient of students whose parents have low income is better than students whose parents have high income. So, it can be concluded that there are differences in the studenst’ adversity quotient whose parents have high income and parents who have low income. Key Words : Adversity Quotient, High Income, Low Income, Online Learning